2012
DOI: 10.1007/s11033-012-2004-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of VKORC1 1639 G>A and CYP2C9*2*3 genotypes in patients that requiring anticoagulant therapy in Turkish population

Abstract: The aim was to investigate the prevalence of VKORC1 and CYP2C9 genotypes in patients requiring anticoagulant therapy in two different region's populations of Turkey. The recent cohort included 292 patients that needed anticoagulant therapy, and who had a history of deep vein thrombosis and/or pulmonary artery thromboembolism. Genomic DNA was isolated from peripheral blood samples and the StripAssay reverse hybridization or Real Time PCR technique was used for genotype analysis. Genotypes for CYP2C9 were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…In our control group, we found the VKORC genotype as 19 (37.3%) for GG, 19 (37.3%) for GA, and 13 (25.5%) for AA alleles. Silan et al 19 found that the genotype of VKORC was detected as follows: 64 (21.9%) for GG, 220 (75.4%) for GA, and 8 (2.7%) for AA alleles 55% in the study conducted in 2012.…”
Section: Discussionmentioning
confidence: 95%
“…In our control group, we found the VKORC genotype as 19 (37.3%) for GG, 19 (37.3%) for GA, and 13 (25.5%) for AA alleles. Silan et al 19 found that the genotype of VKORC was detected as follows: 64 (21.9%) for GG, 220 (75.4%) for GA, and 8 (2.7%) for AA alleles 55% in the study conducted in 2012.…”
Section: Discussionmentioning
confidence: 95%
“…Elde edilen sıklıklara göre olgumuzun bu her iki alele sahip olması toplumda oldukça nadir görülen bir durumdur. [8] Hastamızın öz geçmişinde varfarin kullanımı ile ilişkilendirilmiş gastrointestinal kanama öyküsü olması, düşük doz varfarin kullanmakta iken travma öyküsü olmaksızın sol alt ekstremitede hematom gelişmesi, ayrıca TDP tedavisi sonrası INR değerinin terapötik aralığa gelip varfarin verilmemesine rağmen tekrar yük-selmesi varfarine hassasiyeti artırabilecek gen polimorfizmi olasılığını düşündürdü. Nitekim hastamızın genetik analiz sonucunda CYP2C9*2*3 ve VKORC1 AA ve VKORC1 TT gen polimorfizmine sahip olduğu tespit edildi.…”
Section: Discussionunclassified
“…To date, more than 58 nonsynonymous variants and a series of subvariants of CYP2C9 have been reported (see http://www.imm.ki.se/CYPalleles; access date: Nov. 2014). CYP2C9*2 (430T.C Arg 144 Cys) and CYP2C9*3 (1075A.C Ile 359 Leu) are the most commonly investigated defective alleles, including the characterization of enzymatic activity in vivo and in vitro and population distribution data (García-Martín et al, 2001;Takahashi et al, 2003;Scordo et al, 2004;Scott et al, 2007;Silan et al, 2012;Kraj cíová et al, 2014). Different populations had different frequencies of CYP2C9*2 and CYP2C9*3.…”
Section: Introductionmentioning
confidence: 99%